(untitled) (Cardiovascular Journal, 2017)
Background: Obesity, measured on the basis of body mass index (BMI), is an independent cardiovascular risk factor. However, some studies have reported the obesity paradox after percutaneous coronary intervention (PCI). The relationship between BMI and clinical outcomes after PCI has not been thoroughly investigated, especially in Bangladesh. Method: This cross sectional observational study was conducted at National Institute of Cardiovascular Diseases, on total 100 patients who underwent PCI with two equally divided groups on the basis of BMI of Asian ethnicity: Group I (BMI < 23 kg/m2) and Group II (BMI e 23.0 kg/m2). In-hospital outcomes were observed and recorded after PCI. Results: The mean BMI of study population was 23.9 ± 1.9 kg/m2. The sum of occurrence of adverse in-hospital outcomes was 14.0%. Complications were significantly (p < 0.01) higher in Group I than Group II. Among all adverse in-hospital outcomes, only acute left ventricular failure was found to be statistically significant between groups (p < 0.01). The difference of mean duration of hospital stay after PCI was higher in Group-I which was statistically significant (p < 0.01). Diabetes mellitus and dyslipidemia were found to be the independent predictors for developing adverse in-hospital outcome (OR= 1.68 and 1.46; 95% CI = 1.25 2.24 and 1.16 1.83; p = 0.018 and 0.040, respectively). BMI was inversely associated with adverse in-hospital outcome after PCI (OR = 0.95; 95% CI = 0.91 0.98; p = 0.007). Conclusion: BMI is inversely associated with adverse in-hospital outcomes after PCI. The underweight and normal weight people are at greater risk to experience in-hospital adverse outcomes than overweight and obese people following PCI. Cardiovasc. j. 2017; 10(1): 31-39